Evaluating Educational Marketing Strategies Using the CIPP Model: A Case Study of Student Enrollment Decline in an Islamic Primary School - Wahyu Tukhibul Iman; Nailatul Muna; Milna Wafirah (Journal of Elementary Education Research and Practice, 2025)
Student enrollment sustainability has become a critical challenge for many Islamic primary schools amid increasing competition among educational institutions. This study aims to evaluate the management of educational marketing strategies in attracting new students at MI Ma’arif Ngampeldento Salaman, Central Java, Indonesia. A qualitative case study approach was employed using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through in-depth interviews with the school principal, teachers, committee members, and parents, supported by observations and document analysis. The findings indicate that, contextually, the madrasah has strong socio-religious potential within the Nahdliyin community, yet this advantage has not been translated into effective public visibility. From the input perspective, limited infrastructure, financial constraints, and the absence of a dedicated marketing team hinder strategic implementation. Process evaluation reveals that promotional activities remain conventional, sporadic, and lack systematic digital engagement. Product evaluation shows that while the madrasah offers strong Islamic character-based flagship programs and affordable tuition, these strengths have not been strategically branded or communicated to the wider community. The study concludes that improving institutional competitiveness requires an integrated educational marketing management approach that emphasizes digital-based promotion, strengthening of physical facilities, and strategic branding of flagship programs. These findings contribute to a contextual understanding of educational marketing management in Islamic primary schools facing enrollment decline.